2012
DOI: 10.1007/s00436-012-2932-8
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of pectolinaringenin from Clerodendrum phlomidis L. against Culex quinquefasciatus Say and Aedes aegypti L. (Diptera: Culicidae)

Abstract: Larvicidal activity of 12 fractions and a compound of chloroform extract of Clerodendrum phlomidis L. (Lamiaceae) was assayed for their toxicity against the early fourth-instar larvae of the filarial vector Culex quinquefasciatus Say and dengue vector Aedes aegypti L. The fractions were tested at 100-, 50-, 25- and 12.5-ppm concentrations. The compound pectolinaringenin was tested at 5-, 2.5-, 1.0- and 0.5-ppm concentrations. Among the different fractions, fraction 5 recorded the lowest LC(50) and LC(90) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…In the present study, fraction 2 from the methanol extract of roots of R. cordifolia eluted with hexane:ethyl acetate (90:10) recorded good mosquitocidal activity against A. aegypti followed by fraction 19. LC 50 and LC 90 values for fraction 2 for third instars of C. quinquefasciatus and A. aegypti corroborated earlier findings of Muthu et al (2012) of the potential of plant extracts-Clerodendrum phlomidis-as sources of active molecules with insecticide activity against C. quinquefasciatus and A. aegypti.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, fraction 2 from the methanol extract of roots of R. cordifolia eluted with hexane:ethyl acetate (90:10) recorded good mosquitocidal activity against A. aegypti followed by fraction 19. LC 50 and LC 90 values for fraction 2 for third instars of C. quinquefasciatus and A. aegypti corroborated earlier findings of Muthu et al (2012) of the potential of plant extracts-Clerodendrum phlomidis-as sources of active molecules with insecticide activity against C. quinquefasciatus and A. aegypti.…”
Section: Discussionsupporting
confidence: 86%
“…Extraction, fractionation and isolation of pectolinaringenin Extraction, fractionation and isolation of pectolinaringenin from C. phlomidis were similar as reported by Muthu et al (2012a).…”
Section: Methodssupporting
confidence: 56%
“…Fraction 5 at 1000 ppm and pectolinaringenin at 100 ppm exhibited potent larvicidal activity with least LC 50 values of 198.23 and 27.31ppm, respectively against H. armigera in this investigation. Similarly, Muthu et al (2012a) reported that fraction 5 exhibited LC 50 5.02 and 61.63 ppm and pectolinaringenin LC 50 0.62 and 2.87 ppm against C. quinquefasciatus and A. aegypti, respectively. At lower concentration (12.5 ppm), the compound exhibited more than 38% larval mortality against H. armigera.…”
Section: Larvicidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…quinquefasciatus and A. aegypti (Muthu et al 2012). Similarly, essential oil and their compounds sabinene, biofloratriene, borneol and β-Bisabolol from Clausena dentate (Rutaceae) exhibited larvicidal activity against A. aegypti (Rajkumar and Jebanesan 2010).…”
Section: Mosquito Larvicidal Activitymentioning
confidence: 99%